2018
DOI: 10.3892/mco.2018.1560
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cytoreductive surgery potentially improves the oncological outcomes of patients with recurrent uterine sarcomas

Abstract: Abstract. Uterine sarcomas are some of the most malignant and aggressive tumor types among the gynecologic malignancies, and they are associated with a high rate of recurrence and a poor prognosis. Due to their rarity and diversity, the optimal treatment for recurrent uterine sarcomas has not yet been elucidated. The aim of the present study was to investigate the potential of secondary cytoreductive surgery (SCS) for patients with recurrent uterine sarcomas. A total of 18 patients with recurrent uterine sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Studies have demonstrated that the patients with recurrent uterine sarcomas who underwent secondary cytoreductive surgery had longer overall survival and disease-free intervals following the initial relapse when compared with those treated with chemotherapy or radiotherapy alone. Surgery for extrapulmonary recurrences of uterine sarcomas is limited [9]. Chemotherapy with or without palliative radiation therapy is generally recommended for patients with Stages II and III disease, incompletely resected, or metastatic disease [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the patients with recurrent uterine sarcomas who underwent secondary cytoreductive surgery had longer overall survival and disease-free intervals following the initial relapse when compared with those treated with chemotherapy or radiotherapy alone. Surgery for extrapulmonary recurrences of uterine sarcomas is limited [9]. Chemotherapy with or without palliative radiation therapy is generally recommended for patients with Stages II and III disease, incompletely resected, or metastatic disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary cytoreduction may be considered, as neither chemotherapy nor radiation improved outcomes in recurrent disease [12]. Secondary cytoreduction is associated with prolonged survival in patients with isolated disease recurrence and long progression-free interval from the primary disease [9,13].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients in our series underwent cytoreduction to no residual disease with favorable peri-operative outcomes and encouraging results in terms of survival, when compared with other Original Article series. [9][10][11][12][13][14] Lastly, this study represents one of the largest series of secondary cytoreductive surgery for recurrent uterine leiomyosarcoma in the literature as well as one of the longest follow-up times (online supplementary Table 3). We also recognize the limitations of our study in that it is a retrospective study without a comparison with an analogous group of patients receiving chemotherapy only.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although in a considerable number of patients the disease recurs within the pelvis, some women present with upper abdominal or intra-parenchymal (liver or pulmonary) disease. 9 Evidence in the literature on the management of recurrent uterine leiomyosarcoma is limited and mainly supports the role of secondary cytoreductive surgery, [9][10][11][12][13][14] which can be limited by disease diffusion. In particular, the heterogeneity of tumor histotypes, number of cases, and different rates of cytoreduction represent limitations of previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The same result was achieved in a more recent Japanese retrospective study, which included 18 women with recurrent uterine sarcoma. They found that secondary cytoreductive surgery led to a survival advantage in this group of patients [45].…”
Section: Role Of Surgery In Gynaecological Sarcomasmentioning
confidence: 99%